Economic trends in the transition into a circular bioeconomy - Manfred Kircher (Journal of Risk and Financial Management, 2022)
The shift away from fossil fuels needed to reduce CO2 emissions requires the use of renewable carbon and energy sources, including biomass in the bioeconomy. Already today, the bioeconomy has a significant share in the EU economy with traditionally bio-based sectors. For the future, the energy, mobility and chemical sectors have additional high expectations of the bioeconomy, especially for agriculture and forestry to produce biomass as an industrial feedstock. Numerous studies have been published on the availability of feedstocks, but these often only look at individual applications. Looking at the total demand and considering the sustainability limits of biomass production leads to the conclusion that the expected demand for all industries that could process biomass exceeds the sustainably available capacity. To mitigate this conflict between feedstock demand and availability, it is proposed that the organic chemical sector be fully integrated into the bioeconomy and the energy sector be only partially integrated. In addition, recycling of wastes and residues including CO2 should lead to a circular bioeconomy. The purpose of this manuscript is to help fill the research gap of quantitatively assessing the demand and supply of biomass, to derive economic trends for the current transition phase, and to further develop the theoretical concept of the bioeconomy towards circularity.
Keywords: 330; bioeconomy; biomass; residuals; waste; agriculture; forestry; chemical industry; energy sector; bio-energies; bio-fuel